Addressing career readiness of allergy and immunology fellows in training - Maureen Bauer, MD; Cullen Dutmer, MD; William C. Anderson, III, MD; Dan Atkins, MD (Journal of Allergy and Clinical Immunology: Global, 2025)
Background: Career readiness has been identified as a significant unmet need in allergy and immunology fellowship training programs despite 90% of graduates attending career development sessions provided by local or national societities. Objective: Our aim was to develop and implement a career readiness curriculum for allergy and immunology fellows and assess its effectiveness. Methods: A 6-part career readiness curriculum providing instruction in previously identified areas of deficit was developed in 2021. All sessions were conducted either as individual sessions between the trainee and core faculty or in a small group setting, allowing the curriculum to be customizable for each individual. Quantitative and qualitative assessments were utilized to evaluate the success of the curriculum. Trainees’ comfort and knowledge were assessed via a 7-point Likert scale before and after implementation of the curriculum. To obtain additional feedback, qualitative interviews were conducted with members of each of the first 3 cohorts in which the curriculum was used. Results: Of the 6 trainees who were eligible to participate between 2021 and 2024, all 6 (100%) participated. The trainees’ comfort and knowledge, which were assessed via a 7-point Likert scale, improved after completion of the currkculum. Qualitiative interviews revealed that the curriculums success was due to its customizable nature, which provided individualized feedback. The highest-yield session, as recognized by the trainees, was a discussion panel with recent graduates. It was a supplement to the resources available in other settings. Implementation of a career readiness curriculum contributed to high fellow satisfaction on the annual Accreditation Council for Graduate Medical Education survey. Conclusions: Individualized career planning should be regularly incorporated into graduate medical education training.